Ixekizumab as treatment of erythrodermic psoriasis. Issue 2 (19th February 2021) - Trovato, Emanuele; Orsini, Corinne; Russo, Filomena; Cortonesi, Giulio; Rubegni, Pietro
Abstract: Erytrhodermic psoriasis (EP) is a rare subset of psoriasis that is considered a dermatologic emergency. Due to its limited clinical evidence, pathogenesis is largely unknown and its treatment represents a challenge. Conventional therapies such as methotrexate, cyclosporine, and acitretin are still considered first‐line of treatment but it is necessary to study the efficacy and safety of biologics, including antitumor necrosis factor (TNF), anti‐interleukin (IL)‐23, and anti‐IL17 agents to define new guidelines of treatment. Here, we report two cases of patients with EP treated with ixekizumab.